CLINICAL FEATURES AND PREGNANCY OUTCOMES IN GESTATIONAL DIABETES MELLITUS - Gulrukh Komilovna Karimova; Tolibova Komila Obid qizi (NEW APPROACHES IN EDUCATION: PEDAGOGY, INNOVATION, AND DEVELOPMENT, 2026)
Gestational diabetes mellitus is one of the most common metabolic disorders of pregnancy and is associated with an increased risk of obstetric and perinatal complications [5]. The International Association of Diabetes and Pregnancy Study Groups (IADPSG) has developed updated guidelines for the diagnosis of gestational diabetes mellitus. According to these guidelines, all pregnant women without previously diagnosed diabetes are recommended to undergo an oral glucose tolerance test (OGTT) between 24 and 28 weeks of gestation [1].